Accounting Standards, Cost of Capital, Resource Allocation, and Welfare in a Large Economy - Zhang, Guochang (The Accounting Review, 2013)
ABSTRACT In an extended capital asset pricing model (CAPM) setting, I examine how the quality of accounting standards affects real investment and welfare through its impact on investment hurdle rates. In this model, cash flow uncertainty arises from two fundamental sources relating, respectively, to economic performance and accounting measurement errors, but they combine into a single market factor for asset pricing. Accounting standards matter to real investment not only because information quality affects the required risk premiums on individual projects relative to a given market factor, but also because information quality affects the aggregate investment level and, hence, the market factor itself. I show that improving accounting standards causes both an expansion of the real economy and a shift in capital allocation across firms. While welfare increases as a result, firms in certain risk classes end up with higher costs of capital and lower values, some of which are crowded out from the economy. The study also lends insights into how the real and financial impacts of accounting standards depend on a firm's accounting and economic characteristics.